2014
DOI: 10.1371/journal.pone.0103892
|View full text |Cite
|
Sign up to set email alerts
|

Promoting the Avoidance of High-Calorie Snacks: Priming Autonomy Moderates Message Framing Effects

Abstract: The beneficial effects of gain-framed vs. loss-framed messages promoting health protective behaviors have been found to be inconsistent, and consideration of potential moderating variables is essential if framed health promotion messages are to be effective. This research aimed to determine the influence of highlighting autonomy (choice and freedom) and heteronomy (coercion) on the avoidance of high-calorie snacks following reading gain-framed or loss-framed health messages. In Study 1 (N = 152) participants c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 41 publications
1
19
1
Order By: Relevance
“…Although other research has shown an effect of temporal focus (Gerend and Cullen, 2008), our study demonstrated this only for participants lower in autonomy. We observed no two-way interaction between message frame and autonomy, suggesting that this interaction found in previous research (Churchill and Pavey, 2013;Pavey and Churchill, 2014) may not hold for alcohol consumption when temporal focus is also manipulated. In future research, a 'no temporal focus' condition could be usefully included to attempt to replicate the two-way interaction.…”
Section: Discussioncontrasting
confidence: 71%
See 3 more Smart Citations
“…Although other research has shown an effect of temporal focus (Gerend and Cullen, 2008), our study demonstrated this only for participants lower in autonomy. We observed no two-way interaction between message frame and autonomy, suggesting that this interaction found in previous research (Churchill and Pavey, 2013;Pavey and Churchill, 2014) may not hold for alcohol consumption when temporal focus is also manipulated. In future research, a 'no temporal focus' condition could be usefully included to attempt to replicate the two-way interaction.…”
Section: Discussioncontrasting
confidence: 71%
“…Although we did not directly measure participants' risk perceptions in the current study, our findings may be due to the short-term frame increasing perceptions of risk in the loss-frame message condition for low-autonomy participants, who are thought to already construe a higher risk in conducting the health behavior due to potential threats to their autonomy (see Churchill and Pavey, 2013;Pavey and Churchill, 2014). Further research is needed to test this proposal, and in particular to examine whether the fit between the beliefs of low-autonomy individuals and short-term loss-framed messages result in increased risk perceptions, heightened concern and greater adherence to the recommended health behaviour.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Message framing has been examined in a range of behaviours (Abhyankar et al, 2008;Churchill et al, 2016;Morris et al, 2016;Pavey & Churchill, 2014;Updegraff et al, 2015), and now in a psoriasis population. We demonstrate a clear need for condition-specific health information for people with psoriasis (Keyworth, Nelson, Chew-Graham et al, 2015;Nelson et al, 2017).…”
Section: Implications For Practicementioning
confidence: 99%